Factors Influencing Electronic Data Interchange Adoption among Small and Medium Enterprises in Saudi Arabia - Rawashdeh, Awni; Al-namlah, Lamia (Asian Journal of Business and Accounting, 2017)
Manuscript type: Research paper. Research aims: This paper aims to investigate what factors influence the intention of small and medium enterprises (SMEs) in Saudi Arabia to adopt the electronic data interchange (EDI). Design/ Methodology/ Approach: A survey involving 269 SMEs in Saudi Arabia was conducted and data were analysed using multiple regression. Research findings: Results demonstrate that perceived EDI benefits, organisational readiness, government support and pressure from business partners are significant determinants of the SMEs’ intention to adopt the EDI in Saudi Arabia. Theoretical contribution/ Originality: This study enriches the understanding on the issue of EDI adoption in an Arab country; it specifically fills the lack of academic research that concerns SMEs in Saudi Arabia. Practitioner/ Policy implications: The insights gained from this study can facilitate industry practitioners to develop comprehensive business strategies and effective institutional policies to facilitate EDI implementation in Saudi Arabia. Research limitation/ Implications: The findings of this study may, to some degree, be confounded by external validity since the sampling frame is restricted to SMEs located in Saudi Arabia only. Due to the size of the sample in the study, there is an imperative need for further research to be conducted with a larger sample size. Keywords: Adoption, Electronic Data Interchange (EDI), Innovation, SMEs JEL Classification: M15, M19